Modelling the friction contact in an inertia motor - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric inertia motors, also known as stickslip drives or (smooth) impact drives, use the inertia of a body to drive it by a friction contact in small steps, in the majority of motors composed of a stick phase and a slip phase between the friction partners. For optimizing inertia motors, it is important to understand the friction contact correctly and to measure its properties appropriately. This contribution presents experimental set-ups for measuring the contact force, friction force and relative displacement in an actual inertia motor with a dry friction contact and numerical simulations of the motor operation. The motor uses a pre-stressed multilayer actuator with a displacement in the range of 20 $μ$ m. It is shown that a previously postulated condition for the applicability of simple kinetic friction models is well fulfilled for the investigated motor. The friction contact in the motor is simulated using different kinetic friction models. The input for the friction models is the measured motion of the rod. The models qualitatively reproduce the measured motion but show quantitative deviations varying with frequency. These can be explained by vibrations of the driving rod that are experimentally investigated.
Keywords: Actuator; friction; motor; piezoelectric

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part I: Ideal Excitation. - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Piezoelectric inertia motors, also known as ``stick--slip drives'', use the inertia of a body to drive it in small steps by means of a friction contact. While these steps are classically assumed to involve stiction and sliding, the motors can also operate in ``slip--slip'' mode without any phase of static friction. This contribution provides a systematic investigation and performance comparison of different stick--slip and slip--slip modes of operation. Different criteria for comparing the motional performance of inertia motors are defined: Steady state velocity, smoothness of motion, and start-up time. Using the example of a translational inertia motor excited by an ideal displacement signal, it is found that the maximum velocity reachable in stick--slip operation is limited principally, while continuous slip--slip operation allows very high velocities. For the investigated driving signals, the motor velocity is proportional to the square root of the actuator stroke. The motor performance with these ideal signals defines an upper boundary for the performance of real motors.
Keywords: Inertia motor; Stick--slip drive; Mode of operation; Performance indicator; Velocity maximization; Actuator stroke

Development of a biomedical tissue differentiation system using piezoelectric actuators - Uribe, David Oliva; Stroop, Ralf; Hemsel, Tobias; Wallaschek, Jörg (Frequency Control Symposium, 2008 IEEE International)
In neurosurgery, delineation of tumor boundaries during resection of brain tumors is of substantial relevance. During operation distinction between tumor and healthy tissue rely on the abilities of the surgeon based on visual and tactile differentiation. In this paper a high sensitivity actuator-sensor system using a piezoelectric bimorph is presented. Frequency shift and transfer function of the bimorphpsilas voltages are detected and evaluated. Sensorpsilas sensitivity is evaluated using two frequency controls strategies: A phase-locked loop (PLL) and a self-oscillating circuit. Results of measurements conducted on gel-phantoms are presented and discussed.
Keywords: biomedical measurement; brain; cancer; neurophysiology; phantoms; phase locked loops; piezoelectric actuators; surgery; tactile sensors; transfer functions; tumours; PLL; biomedical tissue differentiation system; brain tumor resection; frequency control; frequency shift; gel-phantom; high sensitivity actuator-sensor system; neurosurgery; phase-locked loop; piezoelectric actuators; piezoelectric bimorph; self-oscillating circuit; sensor sensitivity; tactile differentiation; tactile sensor system; transfer function; tumor boundary; visual differentiation; Biomedical measurements; Circuits; Frequency control; Neoplasms; Neurosurgery; Phase locked loops; Piezoelectric actuators; Surges; Transfer functions; Voltage